Penentuan Jalur Terpendek Evakuasi Bencana Banjir di Kota Manado Menggunakan Algoritma Dijkstra - Lusyane Humune; Jullia Titaley; Mahardika Inra Takaendengan (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2024)
One of the common potential disasters in Manado City is floods. Manado City has a history of destructive floods that damage infrastructure and cause loss of life, resulting in significant losses. Lack of awareness among the public about evacuation locations is also due to the absence of the shortest path for flood evacuation. Therefore, a determination of the shortest path for flood evacuation is made using Dijkstra's Algorithm, which is used to search for graphs in solving the shortest distance problem using distance and time weights from 3 evacuation points and 1 shelter point. Three shortest evacuation routes are found using the Dijkstra algorithm.